An Analysis of Otolaryngology Medical Malpractice Payments From the National Practitioner Data Bank. (21st July 2020) - Breen, Christopher T.; Mehra, Saral
Abstract : Objective: To describe malpractice payments made on behalf of otolaryngologists, analyze trends over time, and test the association of payment amount with severity of alleged malpractice and patient age. Study Design: Retrospective cross‐sectional analysis. Setting: National Practitioner Data Bank. Subjects and Methods: This study comprised all payments made on behalf of otolaryngologists from 1991 to 2018 that were reported to the National Practitioner Data Bank. Descriptive statistics were calculated within and across years. Trends in payments were analyzed with the Mann‐Kendall test. Generalized linear regression was utilized to test for association of payment amount with severity of the alleged injury and patient age. Results: From 1991 to 2018, there was a significant decrease in the number of payments (272 to 81) and number of otolaryngologists on whose behalf payments were made (250 to 77). Mean and median payments increased significantly from 248, 848 to 420, 386 and from 96, 813 to 275, 000, respectively. By severity of alleged injury, mean payments ranged from 39, 755 (95% CI, 20, 957‐75, 412) for insignificant injury to 754, 349 (95% CI, 624, 847‐910, 692) for patients who were left quadriplegic, sustained brain damage, or required lifelong care. By patient age, mean payments for patients ≥60 years old were 191, 465 (95% CI, 159, 880‐229, 292) versus 247, 878 (95% CI, 209, 416‐293, 402) for patients aged 20 to 39 years and 232, 225 (95% CI, 197, 691‐272, 793) for patients aged 40 to 59 years. Conclusion: The annual number and total value of malpractice payments decreased, while the annual mean and median payments increased. Payment amount was associated with severity of alleged malpractice and patient age.